Oral corticosteroid therapy and present disease status in myasthenia gravis. Issue 5 (4th February 2015) - Imai, Tomihiro; Suzuki, Shigeaki; Tsuda, Emiko; Nagane, Yuriko; Murai, Hiroyuki; Masuda, Masayuki; Konno, Shingo; Suzuki, Yasushi; Nakane, Shunya; Fujihara, Kazuo; Suzuki, Norihiro; Utsugisawa, Kimiaki
ABSTRACT: Introduction : The aim of this study was to elucidate the effectiveness of oral prednisolone (PSL) according to dosing regimen in 472 patients with myasthenia gravis (MG). Methods : We compared the clinical characteristics and PSL treatment between 226 patients who achieved minimal manifestations (MM) or better and 246 patients who remained improved (I) or worsened, according to the MG Foundation of America postintervention status. Results : Achievement of MM or better at peak PSL dose (odds ratio 12.25, P  < 0.0001) and combined use of plasma exchange/plasmapheresis (PE/PP) and/or intravenous immunoglobulin (IVIg) (odds ratio 1.92, P  = 0.04) were associated positively, and total PSL dose during the past year (odds ratio 0.17, P  = 0.03) was associated negatively with present MM or better status. Conclusions : Higher PSL dose and longer PSL treatment do not ensure better outcome. In the absence of a good response, the PSL dose should be decreased by combining with modalities such as PE/PP or IVIg. Muscle Nerve 51 :692–696, 2015